Optimization of tannin extraction from coconut coir through response surface methodology. Issue 2 (February 2023) - Sirisangsawang, Rinlada; Phetyim, Natacha
Abstract: Coconut coir is produced by extracting tiny grains of coir from coconut shell, which is an agricultural product that is abundant in Thailand. Coir is typically discarded, but it is a useful material because it contains tannins. Tannin is a polyphenolic compound that is prevalent in the plant kingdom, including in wood, bark, rhizomes, roots, and fruits. In this study, we extracted tannins from coconut coir using two types of solvents: water and ethanol. Optimization of the tannin content was achieved via RSM (response surface methodology) with the assistance of Design-Expert software. Meanwhile, the temperature (30–70 °C), ratio of solid to solvent (1:20–1:40), and solvent type (water or ethanol) were optimized via central composite design (CCD). The optimum model using analysis of variance revealed R 2  = 0.9825, and adj.R 2  = 0.9687. Temperature is affected by tannin content, and high temperatures result in a higher tannin content when using water than when using ethanol. Optimum conditions for coconut coir extraction using water with ethanol include a ratio for solid to solvent of 1:30 and the temperature set to 70 °C. The validated model exhibits errors of 8.24 and 11.08% for water and ethanol, respectively. Confirmation of the presence of tannins in the crude extract was carried out via Fourier-transform infrared spectroscopy and through the use of liquid chromatography with tandem mass spectrometry.